The European Union: security governance and collective securitisation. Issue 2 (23rd February 2019) - Sperling, James; Webber, Mark
Abstract: The EU has long been recognised as a complex security actor with competences across a variety of security-relevant issues. These competences add up to a form of security governance, the purpose of which is to guard against a multiplicity of threats. How threats (and, for that matter, risks) are defined can be seen as the outcome of processes of securitisation where authoritative actors articulate a logic of security – discursively constructing threats and initiating policies in response. This article argues that it is possible for securitisation to occur in a 'collective' setting such as the EU. It articulates a framework through which collective securitisation can be understood – one that is then applied in a series of cases in the remainder of the Special Issue. The ability of the EU to mobilise effort in this regard suggests a resilience overlooked in much of the recent discussion of European crisis.